AIM‐1: An Antibiotic‐Degrading Metallohydrolase That Displays Mechanistic Flexibility. Issue 49 (25th October 2016) - Selleck, Christopher; Larrabee, James A.; Harmer, Jeffrey; Guddat, Luke W.; Mitić, Nataša; Helweh, Waleed; Ollis, David L.; Craig, Whitney R.; Tierney, David L.; Monteiro Pedroso, Marcelo; Schenk, Gerhard
Abstract: Antibiotic resistance has emerged as a major threat to global health care. This is largely due to the fact that many pathogens have developed strategies to acquire resistance to antibiotics. Metallo‐β‐lactamases (MBL) have evolved to inactivate most of the commonly used β‐lactam antibiotics. AIM‐1 is one of only a few MBLs from the B3 subgroup that is encoded on a mobile genetic element in a major human pathogen. Here, its mechanism of action was characterised with a combination of spectroscopic and kinetic techniques and compared to that of other MBLs. Unlike other MBLs it appears that AIM‐1 has two avenues available for the turnover of the substrate nitrocefin, distinguished by the identity of the rate‐limiting step. This observation may be relevant with respect to inhibitor design for this group of enzymes as it demonstrates that at least some MBLs are very flexible in terms of interactions with substrates and possibly inhibitors. Abstract : Synopsis : AIM‐1 is a metallo‐β‐lactamase (MBL) with a broad substrate specificity. A range of physico‐chemical techniques have been employed to demonstrate that both substrates and inhibitors may bind in different modes and locations to the enzyme. The insights gained may pave the way for the development of clinically useful universal MBL inhibitors, an essential strategy to combat antibiotic resistance.